2013
DOI: 10.1021/jp402109p
|View full text |Cite
|
Sign up to set email alerts
|

Optical Response of Lorentzian Nanoshells in the Quasistatic Limit

Abstract: Recently, plexcitonic systems consisting of a plasmonic nanoshell or a core covered by an excitonic shell are engineered. Such systems hold promise for tunable nanophotonic devices for imaging, chemical sensing, and resonance energy transfer. Their plasmonic response is grasped well, while understanding of their excitonic response remains to be improved. To this end, we have developed a methodology in which the functionalities of the dispersive properties of the spherical shell and the nanoenvironment in tunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To understand the core–shell modes, it is necessary to look at the optical properties of Lorentz-material spheres and shells. Dye spheres and shells have for f < 1 one or two resonances, respectively, although the second resonance for the shell appears when the real part of the permittivity becomes negative enough (see Figure S2). For the shell, one resonance remains at the exciton position (slight blue-shift) and the second weak one blue-shifts with increasing f .…”
Section: Resultsmentioning
confidence: 99%
“…To understand the core–shell modes, it is necessary to look at the optical properties of Lorentz-material spheres and shells. Dye spheres and shells have for f < 1 one or two resonances, respectively, although the second resonance for the shell appears when the real part of the permittivity becomes negative enough (see Figure S2). For the shell, one resonance remains at the exciton position (slight blue-shift) and the second weak one blue-shifts with increasing f .…”
Section: Resultsmentioning
confidence: 99%
“…where f is the reduced oscillator strength, ω 0 is the central (angular) frequency of the resonance, ω is the angular frequency, and γ is the damping rate of the resonance. Substitution of Equation ( 7) into Equation ( 6) with re-arrangement for ω gives two solutions for the resonant frequencies (ω) in the limit that γ ω; these can be written as [29],…”
mentioning
confidence: 99%
“…28,29 The response of Lorentzian/excitonic nanoshells with an optically inactive core and embedding medium has been also studied in the quasistatic limit and compared with the properties of the Drude/plasmonic nanoshells. 30 Recently, it has been theoretically shown that a nanosphere of TDBC-doped PVA displays enhanced optical fields and subwavelength field confinement analogously to plasmonic nanoparticles. 31 At present, however, spherical nanoparticles of J-aggregates have not been realized and the synthesis of high-quality nanospheres does not seem readily achievable.…”
mentioning
confidence: 99%
“…It may also occur in the high-energy tail of a strong absorption resonance. For example, it has been shown that lattice vibrations in polar dielectric materials can also originate negative dielectric permittivity in the far- or mid-infrared spectral range, which can support phonon-polaritons confined to the surface. , It has also been shown that in the near-infrared and optical spectral ranges sharp excitonic resonances in organic molecules can originate spectral regions where the dielectric permittivity is negative. , The response of Lorentzian/excitonic nanoshells with an optically inactive core and embedding medium has been also studied in the quasistatic limit and compared with the properties of the Drude/plasmonic nanoshells . Recently, it has been theoretically shown that a nanosphere of TDBC-doped PVA displays enhanced optical fields and subwavelength field confinement analogously to plasmonic nanoparticles .…”
mentioning
confidence: 99%